Does the Release of Bonelli’s Eagles from Captive Breeding Nucleus Contribute to Population Rehabilitation? - Asaf Mayrose (Пернатые хищники и их охрана)
During the late 1960s, the Bonelli’s Eagle (Aquila fasciata) population in Israel was brought to the brink of extinction, due to a combination of factors. A rehabilitation program set in 2000 included few measures, among them the release of eaglets from a captive breeding nucleus, producing two to seven eaglets yearly. In recent years there is an apparent increase in the number of Bonelli’s Eagle pairs breeding in the wild, including the reoccupation of territories that were abandoned for many years. Yet, there is only little evidence for the recruitment of captive-born eagles into the wild population, and their contribution to its growth is unclear.